SISTERLY BONDS IN ALCOTT S LITTLE WOMEN: AN ANALYSIS OF FEMALE SIBLING RELATIONSHIPS - Piri, Melia Debora Sweetzemey; Maru, Mister G.; Olii, Sanerita T. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
Louisa May Alcott s Little Women< em> has been a timeless classic in American literature depicting the lives of the March sisters and their relationships with each other This study analyzes the portrayal of sisterhood and female sibling relationships in Little Women< em> through a feminist lens Using a qualitative content analysis approach the study examines the themes and patterns that emerge in the novel regarding sisterly bonds The findings reveal that the March sisters relationships with each other are characterized by loyalty support and sacrifice reflecting the importance of sisterhood in women s lives The study also highlights the challenges and conflicts that arise in sisterly relationships including jealousy and competition Overall this analysis provides insights into the significance of sisterhood and female sibling relationships in Little Women and their relevance to contemporary feminist discourse < p>